The Relationship between Social Media Usage Activities and the Fulfillment of Activity Daily Living (ADL) in Adolescents in East Java - Pitaloka, Sheilla Dian; Rachmawati, Dhian Satya; Fatimawati, Iis (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2023)
Social media nowadays is not a new thing to society, especially among teenagers. Excessive use of social media can lead to addiction. Adolescents who are addicted can adversely affect the fulfillment of ADL. The purpose of this study was to determine the relationship between the use of social media activities with ADL fulfillment in adolescents in East Java. The research design was observational analytic with a population of 2,827,275 adolescents in East Java and a sample of 139 adolescents aged 12-25 years selected using the proportionate stratified sampling technique. The variables consist of activities using social media and fulfilling ADL. The measuring instrument used is the SIPMS questionnaire and the ADL fulfillment questionnaire. Test analysis using Spearmen Rho (Sig. 0.05) The results showed that most of the adolescents used social media in the medium intensity category as many as 97 people (69,3%) and 92 people (65,7%). The results showed that there was a unidirectional relationship between the use of social media activities and the fulfillment of ADL in adolescents = 0.000 with the results of r = 0.424. The use of social media with high intensity does not have a negative impact on the fulfillment of ADL adolescents. The role of health workers and education personnel is to provide education to adolescents about efficient time management so that ADL can be fulfilled properly even with a high intensity of social media use.